Pembuatan Komik Layanan Perpustakaan Keliling di Dinas Perpustakaan dan Kearsipan Kota Padang untuk Sekolah Dasar dengan Menggunakan Aplikasi Komik Manga Maker - Sari, Lili Purnama; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractÂ Research methods used in the manufacture of the paper is descriptive method in the form of the written word of the document are observed is done by means of observation and interviews. The observation is done to obtain data about a travelling library in the service of the library and Archives of the city of Padang. Data collection with interviews done by librarians of the library and Archives Department of the city of Padang. On the basis of the discussion it can be concluded that the stage of the round-the-comic library services library and Archives Office of Padang City elementary school for application of manga maker, as follows: 1) prepares tools and materials; 2) determine which ideas or creative idea; 3) determines a theme or story gendre; 4) determine the figure or figures in a story; 5) create a script of the story; 6) illustrates the comic sketches; 7) make the balloon text conversations and in comics; 8) manufacture of comic cover; 9) comic results storage. After the stage finish, then the comics be printed and then read and utilized by the students.Keywords: comic, mobile library service, primary school.